Morphological diversity determination of the tomato fruit collection (Solanum lycopersicum L.) by phenotyping based on digital images - Gonzalo Quispe-Choque; Shirley Rojas-Ledezma; Amalia Maydana-Marca (Journal of the Selva Andina Research Society)
Germplasm characterization is an effective way to unravel morphological diversity in vegetative and fruit characters. This study was conducted to determine diversity in tomato (Solanum spp.) fruits using eight conventional descriptors (CD) and 47 Tomato Analyzer (TA) software descriptors related to fruit morphometry. Phenotyping was carried out on 50 accessions selected for morphological variation from the National Genetic Resources Bank. Variability was detected for fruit characteristics with CD and quantified by TA. Fruit shape was the main character used for visual grouping of accessions into ten different varietal groupings of shape: Circular (26 %), Flattened (20 %), Oboval (20 %), Pyriform (12 %), Elliptical (6 %), Chordate (6 %), Cylindrical (4 %), Oblong (2 %), Oval (2 %) and Flattened (2 %) and from very small to large size. Significant variation was observed for fruit weight (3.75-217.44 g), equatorial diameter (17.85-75.55 mm), polar diameter (17.57-96.76 mm), circumference (61.86-312.64 mm) and area (249.56-6367.57 mm). Principal component analysis contributed to the total variation and the first two explained 30.02 % of the variation where fruit shape index and proximal/distal end shape of the fruit showed high contribution in the variation of the first component. There was a strong positive correlation between fruit shape and fruit size, while negative correlations were between fruit shape index, internal eccentricity and proximal end shape. The results have shown that TA software descriptors and CD are a powerful tool for characterising and classifying tomato landraces, as well as for distinguishing between groups of related cultivars. This has important implications for the breeding and protection of tomato landraces.